SARANA PENGEMBANGAN MODE STREETWEAR DI JAKARTA - Rivaldo Mark Frans Valentino Tumbelaka; Suryono Herlambang (Jurusan Arsitektur dan Perencanaan, 2021)
Along with the rapid development of the creative fashion industry in Indonesia, fashion designers are required to be more creative to compete internationally. Streetwear has become a fashion stream loved by millennials & gen-z in the city of Jakarta. Lack of space to accommodate their creativity in the city of Jakarta is the problem of this project. Tebet area is an area located in South Jakarta, Kelurahan Tebet, South Jakarta city. The Tebet area has developed quite rapidly. This area is surrounded by commercial office buildings. This area is surrounded by streetwear fashion distros, some have been developing for a long time and some are just starting to enter the fashion industry. As the streetwear fashion industry develops in Indonesia, it can improve Indonesia's economy, but it can also become a boomerang due to the government's lack of attention to increase the creative streetwear fashion sector. The Tebet area is very suitable to respond to this problem because with the surrounding fashion distributions it can be concentrated into a fashion hub to work and collaborate. Keywords: Community; Public; Tebet; Streetwear AbstrakSeiring berkembang pesatnya industri kreatif fashion di Indonesia, para fashion designer dituntut untuk lebih kreatif untuk bersaing secara internasional. Streetwear sudah menjadi aliran fashion yang digandrungi oleh millenial dan gen-z di kota Jakarta. Kurangnya tempat untuk mewadahi kreatifitas mereka di kota Jakarta menjadi permasalahan proyek ini. Kawasan Tebet adalah suatu kawasan yang berlokasi di Jakarta Selatan, Kelurahan Tebet, kota Jakarta Selatan. Kawasan Tebet sudah berkembang lumayan pesat. Kawasan ini dikelilingi oleh bangunan perkantoran komersil. Kawasan ini dikelilingi oleh fashion distro streetwear, ada yang sudah lama berkembang dan ada juga baru mulai memasuki industri fashion. Seiring berkembangnya industri fashion streetwear di Indonesia, itu bisa menaikan perekonomian Indonesia, tetapi itu bisa juga menjadi boomerang karena kurangnya perhatian dari pemerintah untuk menaikan sektor kreatif fashion streetwear. Daerah Tebet sangat cocok untuk merespon masalah ini karena dengan adanya fashion distro disekilingnya itu bisa dipusatkan ke dalam fashion hub untuk berkarya dan berkolaborasi.